2020
DOI: 10.1371/journal.pone.0229206
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the binding properties of the anti-PD-1 antibody landscape using label-free biosensors

Abstract: Here we describe an industry-wide collaboration aimed at assessing the binding properties of a comprehensive panel of monoclonal antibodies (mAbs) against programmed cell death protein 1 (PD-1), an important checkpoint protein in cancer immunotherapy and validated therapeutic target, with well over thirty unique mAbs either in clinical development or market-approved in the United States, the European Union or China. The binding kinetics of the PD-1/mAb interactions were measured by surface plasmon resonance (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Care is needed in making comparisons especially given the considerable discrepancies in the literature for the anti-PD-1 antibody binding constants, as indicated in Table 2 . 15–17 In general, it is best to compare drug-target interactions within the same platform using consistent experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Care is needed in making comparisons especially given the considerable discrepancies in the literature for the anti-PD-1 antibody binding constants, as indicated in Table 2 . 15–17 In general, it is best to compare drug-target interactions within the same platform using consistent experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reported that 3D hydrogels systematically produce slower apparent on-rates ( k a values) than those on planar chips. 5 HC-30M is nearly planar as it is composed of short-hair (30 nm) unbranched polycarboxylate, compared with the Biacore CM5 chip, which is a complex branched carboxymethyl 3D hydrogel with a height of approximately 200 nm. Any differences between the two chip types were likely minimal in this study because the on-rates of the FAb interactions were relatively slow (<1 × 10 5 M −1 s −1 ), as chip type becomes more of a differentiator for binding interactions with fast on-rates that approach mass transport limitation.…”
Section: Resultsmentioning
confidence: 99%
“…6 That study (and others) also aimed to compare affinity determinations produced by solution and surface methods. 7 Other benchmark studies engaged many participants using various SPR biosensor platforms without mandating experimental protocols 812 to assess overall the performance of the scientific community to produce reliable affinity measurements with minimal experimental guidance.…”
Section: Resultsmentioning
confidence: 99%
“…Although a few drugs have novel mechanisms of action (e.g., dual targeting of PD-1/TIM-3, PD-L1/CTLA-4), these drugs largely target the same pathway. Although the unique binding properties of PD-(L)1 antibodies have been reported, 6 it is unknown whether the subtle differences in binding profiles translate into clinically meaningful differences in patient outcomes. Some studies suggest that the differences in clinical outcomes in clinical trial results between anti–PD-(L)1 agents are more likely because of trial design–related factors than differences in the mechanism of action or pharmacodynamics of the drugs.…”
Section: Discussionmentioning
confidence: 99%